Android Trainer Wawancara Pekerjaan Dalam Bahasa Inggris Menggunakan Audio Visual Dengan Metode Prototype - Dentik Karyaningsih; Diki Susandi; Erina Juwita (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Job competition is getting tougher after the implementation of the ASEAN Economic Community. Prospective workers are required to have competence at work and be skilled at communicating using international languages, especially English. Based on the results of the questionnaire on 100 data samples using google form, there are as many as 50% having difficulty when interviewing using English. So this study is proposed to improve English pronunciation skills during job interviews. Android Trainer is self-training using the Android Platform. It is designed using Google Speech API and Speech Recognition Technology. It is displayed using Audio Visual and the development method uses the Prototype method. The result of this research is the Android Trainer which is a smart solution to make it easier to practice independently at any time. So that it can improve English pronunciation skills. This is useful when going through the interview process using English at various types of companies during the employee recruitment process.